Titanium mesh surface multilayer composite oxide protective coating and thermal decomposition preparation method

CN122979882APending Publication Date: 2026-10-27深圳铱创科技股份有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611474721.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-21
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]然而,现有钛网钌铱氧化物防护涂层仍存在明显短板:一是贵金属钌、铱用量偏高,涂层制备成本居高不下,难以大规模工程应用;二是涂层与钛网基体、以及多层涂层之间热膨胀系数差异较大,烧结制备与温度波动服役过程中易产生层间热失配与界面应力,引发涂层开裂、剥落,尤其在强腐蚀交变工况下,涂层界面结合力不足的问题尤为突出,钛网构件的长期服役稳定性难以保障,现有涂层体系多缺少兼具氧阻隔、导电增强和应力缓冲功能的底层与中间层,难以同时满足界面结合强度、导电稳定性和长期耐蚀防护需求

Benefits of technology

通过在钛网表面依次构建Sb-SnO2-TiO2混合氧化物底层、Ti4O7-TiO2混合氧化物中间层和RuO2-IrO2-TiO2混合氧化物表层,利用底层改善涂层与钛网基体的结合力,利用中间层缓冲底层与表层之间的热膨胀差异和烧结应力,从而减少涂层开裂和剥落,提高涂层整体性和界面结合强度;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979882A_ABST
    Figure CN122979882A_ABST
Patent Text Reader

Abstract

The application discloses a kind of titanium mesh surface multilayer composite oxide protective coating and thermal decomposition preparation method, by sequentially forming Sb-SnO2-TiO2 mixed oxide bottom layer, Ti4O7-TiO2 mixed oxide intermediate layer and RuO2-IrO2-TiO2 mixed oxide surface layer on the surface of titanium mesh;Bottom layer and surface layer sintering temperature is 480~520 ℃, and intermediate layer sintering temperature is 530~570 ℃, with Ti4O7-TiO2 intermediate layer as conductive reinforcing layer and stress buffer layer, utilize non-noble metal oxide part to replace noble metal, reduce the amount of noble metal while maintaining chlorine activity, improve the adhesion of coating and titanium matrix, prolong the accelerated corrosion life of coating sample.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal surface oxide coating preparation technology, and particularly to a multilayer composite oxide protective coating for titanium mesh surface and a thermal decomposition preparation method. Background Technology

[0002] Oxide protective coatings on titanium mesh surfaces are one of the core technologies for surface strengthening of titanium mesh components. Titanium and titanium alloys, due to their excellent specific strength and corrosion resistance, are widely used in structural components subjected to various highly corrosive conditions, such as chemical corrosion protection, flue gas desulfurization, marine engineering, and high-salt corrosion environments. Preparing oxide protective coatings on their surfaces can further expand their service environment and extend their service life. Among these, ruthenium-iridium multi-component composite oxide coatings, due to their excellent corrosion resistance, controllable composition, and mature process route using thermal decomposition, have become one of the mainstream technical solutions for titanium mesh surface protection.

[0003] Traditional titanium mesh oxide protective coatings mostly use ruthenium-based or ruthenium-iridium-based multi-element oxide systems, which are coated onto the titanium mesh surface through thermal decomposition. RuO2 itself has good electrical conductivity and corrosion resistance, but its resistance to corrosion and oxidation is limited in high-temperature corrosive environments with strong acids and high chloride ions. Under long-term service, corrosive media can easily penetrate to the substrate surface through microscopic defects in the coating, causing passivation of the titanium substrate, blistering and peeling of the coating, and limiting the protective life. Introducing IrO2 can improve the phase stability and corrosion resistance of the oxide to a certain extent, reduce the interfacial resistance, and delay the functional degradation of the coating.

[0004] However, existing ruthenium-iridium oxide protective coatings for titanium mesh still have significant shortcomings: First, the amount of precious metals ruthenium and iridium used is too high, resulting in high coating preparation costs and making large-scale engineering applications difficult; second, the difference in thermal expansion coefficients between the coating and the titanium mesh substrate, as well as between multiple layers of coating, is large, which easily leads to interlayer thermal mismatch and interfacial stress during sintering and temperature fluctuations in service, causing coating cracking and peeling. Especially under strong corrosive alternating conditions, the problem of insufficient interfacial adhesion is particularly prominent, making it difficult to guarantee the long-term service stability of titanium mesh components. Existing coating systems often lack bottom and intermediate layers that combine oxygen barrier, conductivity enhancement, and stress buffering functions, making it difficult to simultaneously meet the requirements of interfacial bonding strength, conductivity stability, and long-term corrosion resistance.

[0005] Therefore, optimizing the interfacial bonding strength of multilayer oxide coatings on titanium mesh surfaces, alleviating interlayer thermal stress mismatch, and improving long-term protective performance under highly corrosive environments are technical problems that urgently need to be solved in this field. Summary of the Invention

[0006] The main objective of this invention is to provide a multilayer composite oxide protective coating for titanium mesh and a method for its thermal decomposition preparation. By buffering interlayer lattice mismatch and sintering thermal stress through an intermediate layer, the interfacial bonding strength, electrical conductivity stability, and corrosion barrier properties of the coating are simultaneously improved.

[0007] To address the aforementioned technical problems, this invention provides a method for preparing a multilayer composite oxide protective coating on a titanium mesh surface by thermal decomposition, comprising the following steps: S1, perform surface pretreatment on the titanium mesh to obtain a pretreated titanium mesh; S2, an antimony-tin-titanium precursor solution is coated on the surface of a pretreated titanium mesh, dried and sintered in an air atmosphere at 480~520℃. The coating, drying and sintering are repeated multiple times to form a mixed oxide underlayer of Sb-SnO2-TiO2 on the surface of the titanium mesh. S3, a mixed slurry containing titanium heptoxide and a titanium source is coated on the surface of the Sb-SnO2-TiO2 mixed oxide bottom layer, dried and sintered in an air atmosphere at 530~570℃, and the coating, drying and sintering are repeated multiple times to form a Ti4O7-TiO2 mixed oxide intermediate layer. The mixed slurry was prepared by adding Ti4O7 powder and tetrabutyl titanate in anhydrous ethanol at a mass ratio of 4:6 to 6:4, adding polyvinylpyrrolidone, and then dispersing and stirring with ultrasound and magnetic force. The mixed slurry is coated onto the surface of the Sb-SnO2-TiO2 mixed oxide substrate, dried at 100°C for 8-12 minutes, and then placed in a muffle furnace for air atmosphere sintering. The sintering time for each sintering is 25-35 minutes. S4, a ruthenium-iridium-titanium precursor solution is coated on the surface of the Ti4O7-TiO2 mixed oxide intermediate layer, dried, and then sintered in an air atmosphere at 480~520℃. The coating, drying, and sintering are repeated multiple times to form a RuO2-IrO2-TiO2 mixed oxide surface layer.

[0008] Furthermore, in step S2, the molar ratio of Sb, Sn, and Ti in the antimony-tin-titanium precursor solution is 10:90:20 to 10:90:30.

[0009] Furthermore, the antimony-tin-titanium precursor solution in step S2 is prepared by dissolving antimony trichloride, tin tetrachloride and tetrabutyl titanate in a mixed solvent of isopropanol and n-butanol, and then adding concentrated hydrochloric acid.

[0010] Furthermore, in step S4, the molar ratio of Ru, Ir, and Ti in the ruthenium-iridium-titanium precursor solution is 25:20:55.

[0011] Furthermore, the coating method in steps S2 and S4 is brush coating, the drying temperature is 95℃~105℃, the drying time is 8~12min, and the single sintering time is 25~35min.

[0012] Furthermore, step S1 includes: The titanium mesh was sandblasted with 60-mesh white corundum to control the surface roughness Ra to be 5μm~7μm; The sandblasted titanium mesh was placed in an environment of 480℃~520℃ for 40min~50min for stress relief heat treatment, and then cooled to room temperature in the furnace. Prepare an oxalic acid solution with a mass fraction of 5%–7% and pickle the titanium mesh at 80℃–90℃ for 2.5h–3.5h. After pickling, the titanium mesh is ultrasonically cleaned with pure water 3 to 5 times, with each cleaning session lasting 10 to 14 minutes. Then it is dried in an environment of 65℃ to 75℃ to obtain the pretreated titanium mesh.

[0013] Furthermore, in step S2, the coating, drying, and sintering are repeated 2 to 4 times; in step S3, the coating, drying, and sintering are repeated 2 to 4 times; and in step S4, the coating, drying, and sintering are repeated 7 to 9 times.

[0014] The present invention also provides a multilayer composite oxide protective coating on the surface of a titanium mesh, comprising: Titanium mesh; The titanium mesh is sequentially covered with a bottom layer of Sb-SnO2-TiO2 mixed oxide, an intermediate layer of Ti4O7-TiO2 mixed oxide, and a top layer of RuO2-IrO2-TiO2 mixed oxide.

[0015] Furthermore, in the bottom layer of the Sb-SnO2-TiO2 mixed oxide, the molar ratio of Sb, Sn, and Ti is 10:90:20 to 10:90:30; in the surface layer of the RuO2-IrO2-TiO2 mixed oxide, the molar ratio of Ru, Ir, and Ti is 25:20:55.

[0016] Furthermore, the Ti4O7-TiO2 mixed oxide intermediate layer is prepared by sintering Ti4O7 powder and tetrabutyl titanate at a mass ratio of 4:6 to 6:4.

[0017] The thermal decomposition preparation method of the multilayer composite oxide protective coating on the surface of titanium mesh provided by the present invention has the following beneficial effects: By sequentially constructing an Sb-SnO2-TiO2 mixed oxide underlayer, a Ti4O7-TiO2 mixed oxide intermediate layer, and a RuO2-IrO2-TiO2 mixed oxide surface layer on the surface of a titanium mesh, the underlayer improves the adhesion between the coating and the titanium mesh substrate, and the intermediate layer buffers the thermal expansion difference and sintering stress between the underlayer and the surface layer, thereby reducing coating cracking and peeling, and improving the overall integrity and interfacial bonding strength of the coating. By using a Ti4O7-TiO2 mixed oxide as the intermediate layer, where Ti4O7 has high conductivity and TiO2 exists as a stable phase, the intermediate layer has both conductivity enhancement and stress buffering effects, which is beneficial to reduce coating resistance, improve the electron transport capability in the conductive coating, and avoid interface defects caused by excessive lattice mismatch between the intermediate layer and the adjacent layer. By introducing non-precious metal elements such as tin, antimony, and titanium into the Sb-SnO2-TiO2 bottom layer and Ti4O7-TiO2 intermediate layer, the amount of ruthenium and iridium used in the surface layer is reduced. While maintaining the conductivity and corrosion resistance of the coating, the cost of coating materials and the amount of precious metals used are reduced, which is beneficial to extending the protective life of titanium mesh in highly corrosive environments. Attached Figure Description

[0018] Figure 1 This is a flowchart of a thermal decomposition preparation method for a multilayer composite oxide protective coating on a titanium mesh surface provided in an embodiment of the present invention; Figure 2 This is a SEM image of the intermediate layer prepared in Example 1 of the present invention; Figure 3 This is a SEM image of the surface layer prepared in Example 1 of the present invention; Figure 4 These are electrochemical polarization potential data graphs from the embodiments and comparative examples of this invention; Figure 5 These are accelerated corrosion lifetime test diagrams from the embodiments and comparative examples of the present invention; The realization of the objective, functional features and advantages of the present invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation

[0019] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0020] Reference Figure 1 This is a schematic flowchart of a thermal decomposition preparation method for a multilayer composite oxide protective coating on a titanium mesh surface proposed in this invention, including the following steps: S1, perform surface pretreatment on the titanium mesh to obtain a pretreated titanium mesh; S2, an antimony-tin-titanium precursor solution is coated on the surface of a pretreated titanium mesh, dried and sintered in an air atmosphere at 480~520℃. The coating, drying and sintering are repeated multiple times to form a mixed oxide underlayer of Sb-SnO2-TiO2 on the surface of the titanium mesh. S3, a mixed slurry containing titanium heptoxide and a titanium source is coated on the surface of the Sb-SnO2-TiO2 mixed oxide bottom layer, dried and sintered in an air atmosphere at 530~570℃, and the coating, drying and sintering are repeated multiple times to form a Ti4O7-TiO2 mixed oxide intermediate layer. The mixed slurry was prepared by adding Ti4O7 powder and tetrabutyl titanate in anhydrous ethanol at a mass ratio of 4:6 to 6:4, adding polyvinylpyrrolidone, and then dispersing and stirring with ultrasound and magnetic force. The mixed slurry is coated onto the surface of the Sb-SnO2-TiO2 mixed oxide substrate, dried at 100°C for 8-12 minutes, and then placed in a muffle furnace for air atmosphere sintering. The sintering time for each sintering is 25-35 minutes. S4, a ruthenium-iridium-titanium precursor solution is coated on the surface of the Ti4O7-TiO2 mixed oxide intermediate layer, dried, and then sintered in an air atmosphere at 480~520℃. The coating, drying, and sintering are repeated multiple times to form a RuO2-IrO2-TiO2 mixed oxide surface layer.

[0021] As described in step S1 above, the titanium mesh pretreatment focuses on surface roughening, stress relief, and oxide film removal to ensure a stable bond between the oxide coating and the titanium substrate. The titanium mesh is sandblasted using 60-mesh white corundum to control the surface roughness Ra to 5μm–7μm, creating a uniform micro-uneven structure on the substrate surface to provide stable mechanical interlocking sites for coating adhesion. After sandblasting, the titanium mesh is placed in a heating device and held at 480℃–520℃ for 40–50 minutes to complete stress-relief heat treatment. After treatment, it is cooled to room temperature with the furnace to eliminate residual internal stress introduced during sandblasting and prevent substrate deformation during high-temperature sintering. A 5%–7% oxalic acid solution is prepared, and the heat-treated titanium mesh is completely immersed in the solution, with the solution temperature controlled at 80℃–90℃, for continuous acid washing for 2.5–3.5 hours. Oxalic acid solution is used to micro-etch the surface of the titanium substrate, completely removing the original oxide film and forming a uniform textured surface, further enhancing the adhesion between the coating and the substrate. After acid etching, the titanium mesh is removed and ultrasonically cleaned with pure water, repeated 3-5 times, with each cleaning session lasting 10-14 minutes, to thoroughly remove residual acid and etching products from the surface. After cleaning, the titanium mesh is dried at 65℃-75℃ to obtain the pretreated titanium mesh.

[0022] As described in step S2 above, the antimony-tin-titanium mixed oxide underlayer is used to construct a conductive barrier transition structure between the titanium substrate and the functional coating, simultaneously achieving interface bonding strengthening and substrate passivation suppression. Antimony trichloride, tin tetrachloride, and tetrabutyl titanate are weighed according to a molar ratio of Sb, Sn, and Ti of 10:90:20 to 10:90:30, dissolved in a mixed solvent of isopropanol and n-butanol, and concentrated hydrochloric acid is added to adjust the system stability. The mixture is stirred continuously until the solute is completely dissolved, yielding a clear and homogeneous antimony-tin-titanium precursor solution. The precursor solution is uniformly coated onto the surface of a pretreated titanium mesh using a brush coating method. After coating, the sample is dried at 95℃ to 105℃ for 8 to 12 minutes to allow the solvent to fully evaporate. The dried sample is then placed in a muffle furnace and sintered at 480℃ to 520℃ in air for 25 to 35 minutes to allow the metal salt to fully decompose and generate the corresponding oxide. Repeated coating, drying, and sintering operations 2–4 times form a uniformly thick Sb-SnO2-TiO2 mixed oxide underlayer on the titanium mesh surface. This underlayer possesses both good electronic conductivity and oxygen barrier properties, effectively preventing oxygen atoms from diffusing into the titanium substrate during corrosion or oxidation, avoiding the formation of a high-resistance titanium oxide passivation layer on the substrate surface, and simultaneously providing a dense oxide bonding substrate for the upper intermediate layers.

[0023] As described in step S3 above, the Ti4O7-TiO2 mixed oxide intermediate layer connects the bottom layer and the top layer, undertaking multiple functions such as stress buffering, conductivity enhancement, and oxygen barrier, and is the core structure for improving the overall service stability of the coating. Ti4O7 powder and tetrabutyl titanate were weighed at a mass ratio of 4:6 to 6:4, mixed in anhydrous ethanol, and polyvinylpyrrolidone was introduced as a dispersing agent. After ultrasonic dispersion and magnetic stirring, a uniformly dispersed slurry with good sedimentation stability was obtained. The slurry was uniformly coated onto the surface of the Sb-SnO2-TiO2 mixed oxide bottom layer using a brush coating method. After coating, the sample was dried at 100℃ for 8 to 12 minutes to allow the ethanol solvent to fully evaporate. The dried sample was then transferred to a muffle furnace and sintered at 530℃ to 570℃ for 25 to 35 minutes in air. The tetrabutyl titanate pyrolyzed at high temperature to generate TiO2, which acts as a binder phase to form a dense composite structure with the Ti4O7 particles. The coating, drying, and sintering processes were repeated three times to form a uniformly thick Ti4O7-TiO2 mixed oxide intermediate layer on the bottom surface. This intermediate layer can match the thermal expansion coefficients of the upper and lower layers, alleviate interlayer thermal stress during the sintering process and service stage, reduce the risk of coating peeling, and at the same time maintain efficient electron transport due to the high conductivity of Ti4O7, further enhance oxygen barrier capability, and provide a stable supporting substrate for the surface coating.

[0024] As described in step S4 above, the RuO2-IrO2-TiO2 mixed oxide surface layer serves as a conductive and corrosion-resistant functional layer, directly determining the conductive stability and protective lifespan of the coating. Ruthenium trichloride, chloroiridic acid, and tetrabutyl titanate are weighed according to the molar ratio of Ru, Ir, and Ti elements of 25:20:55 and dissolved in a mixed solvent of n-butanol and isopropanol. The mixture is stirred continuously until the solute is completely dissolved to obtain a clear and uniform ruthenium-iridium-titanium precursor solution. The precursor solution is uniformly coated onto the surface of the Ti4O7-TiO2 mixed oxide intermediate layer by brushing. After coating, the mixture is placed in an environment of 95℃~105℃ to dry for 8min~12min to allow the solvent to fully evaporate. The dried samples were placed in a muffle furnace and sintered in air at 480℃~520℃ for 25min~35min to allow the noble metal salt and titanium source to fully pyrolyze and generate a composite oxide phase. This coating, drying, and sintering process was repeated 7~9 times to form a uniform RuO2-IrO2-TiO2 mixed oxide surface layer on the intermediate layer. This surface layer possesses both good electrical conductivity and resistance to electrochemical corrosion, effectively reducing interfacial resistance. Relying on the stress buffer and conductive support of the underlying intermediate layer, it effectively mitigates coating peeling and performance degradation under cyclic operating conditions, ensuring the long-term conductive protection performance and structural stability of the coating.

[0025] The present invention will be specifically described below through examples and comparative examples.

[0026] Example 1: Industrial pure titanium mesh was selected as the substrate and its surface was pretreated. The titanium mesh was sandblasted with 60-mesh white corundum to control the surface roughness Ra to 5μm–7μm. After sandblasting, the titanium mesh was placed in a muffle furnace and subjected to stress-relief heat treatment at 480℃–520℃ for 40–50 minutes, followed by furnace cooling to room temperature. A 5%–7% oxalic acid solution was prepared, and the heat-treated titanium mesh was completely immersed in the solution. The solution temperature was controlled at 80℃–90℃, and acid washing was continued for 2.5–3.5 hours. After acid washing, the titanium mesh was removed and ultrasonically cleaned with pure water 3–5 times, with each cleaning session lasting 10–14 minutes. It was then dried at 65℃–75℃ to obtain the pretreated titanium mesh.

[0027] Antimony trichloride, tin tetrachloride, and tetrabutyl titanate were weighed according to a molar ratio of Sb:Sn:Ti of 10:90:20 and dissolved in a mixed solvent of isopropanol and n-butanol. Concentrated hydrochloric acid was added to adjust the stability of the system, and the mixture was stirred until the solutes were completely dissolved to obtain an antimony-tin-titanium precursor solution. The precursor solution was uniformly coated onto the surface of a pretreated titanium mesh using a brush coating method. After coating, the mesh was dried at 100℃ for 8-12 minutes and then sintered in a muffle furnace at 480℃-520℃ for 25-35 minutes in air. This coating, drying, and sintering process was repeated three times to form an Sb-SnO2-TiO2 mixed oxide underlayer on the surface of the titanium mesh.

[0028] Weigh the materials according to a Ti4O7 powder to tetrabutyl titanate mass ratio of 6:4, add them to anhydrous ethanol and mix. Introduce polyvinylpyrrolidone as a dispersing agent, and after ultrasonic dispersion and magnetic stirring, obtain a uniformly dispersed mixed slurry. The mixed slurry is uniformly coated onto the surface of the Sb-SnO2-TiO2 mixed oxide underlayer by brushing. After coating, dry at 100℃ for 8 min to 12 min, and then transfer it to a muffle furnace for sintering at 530℃ to 570℃ in air atmosphere for 25 min to 35 min. Repeat the coating, drying and sintering operation 3 times to form the Ti4O7-TiO2 mixed oxide intermediate layer.

[0029] Ruthenium trichloride, chloroiridic acid, and tetrabutyl titanate were weighed according to a Ru:Ir:Ti molar ratio of 25:20:55 and dissolved in a mixed solvent of n-butanol and isopropanol. The solution was stirred until the solutes were completely dissolved to prepare a ruthenium-iridium-titanium precursor solution. The precursor solution was uniformly coated onto the surface of the Ti4O7-TiO2 mixed oxide intermediate layer by brushing. After coating, the solution was dried at 100℃ for 8-12 minutes and then sintered in a muffle furnace at 480℃-520℃ for 25-35 minutes in air atmosphere. The coating, drying, and sintering operations were repeated 8 times to form a RuO2-IrO2-TiO2 mixed oxide surface layer, finally obtaining a titanium mesh-based multilayer composite oxide protective coating sample.

[0030] The morphology of the coating prepared in this embodiment was characterized, and the surface scanning electron microscope morphology of the Ti4O7-TiO2 mixed oxide intermediate layer is as follows: Figure 2 As shown, the intermediate layer exhibits a continuous sintered structure, with the coating completely covering the substrate surface. The particles, sintered at high temperature, form irregular aggregates with uniformly distributed microcracks and pores between the clusters. This rough surface structure provides ample mechanical interlocking sites for the upper surface coating. The surface scanning electron microscope morphology of the RuO2-IrO2-TiO2 mixed oxide layer is shown in the figure. Figure 3 As shown, the surface layer exhibits a typical pyrolysis composite oxide mud crack morphology. The coating is continuous and intact as a whole, with uniformly distributed cracks on the surface. Under high magnification, nano-sized noble metal oxide grains can be seen dispersed in the titanium oxide matrix. The two phases are uniformly mixed, which can provide a uniform bearing interface for the surface coating.

[0031] Electrochemical polarization testing was performed on the coating prepared in this embodiment. An electrochemical test cell was used, with the coating sample as the working coating sample, a platinum sheet as the reference coating sample, and a saturated calomel coating sample as the reference coating sample. The test medium was a corrosive electrolyte, and the test temperature was controlled at a set temperature. The electrochemical polarization potential of the coating sample was measured using the constant current method. The test results are as follows: Figure 4As shown, the electrochemical polarization potential of the sample in this embodiment is 1.087V, which is at a low level, indicating that the coating has good conductivity and electrochemical stability.

[0032] The coating prepared in this embodiment was subjected to accelerated corrosion lifetime testing. The accelerated corrosion lifetime of the coating was tested using a constant current accelerated corrosion method. The etching solution was a 1 mol / L sulfuric acid solution, and the test current density was 10000 A / m². The cumulative energized time of the coating sample was recorded. The test results are as follows: Figure 5 As shown, the accelerated corrosion lifetime of the sample in this embodiment reached 221 hours, which is the best value among all tested samples.

[0033] Example 2: The surface pretreatment steps of the titanium mesh in this example are the same as those in Example 1, resulting in a pretreated titanium mesh.

[0034] The core difference between this embodiment and Example 1 lies in the elemental ratio of the bottom precursor: antimony trichloride, tin tetrachloride and tetrabutyl titanate were weighed according to the molar ratio of Sb, Sn and Ti elements of 10:90:30 to prepare the antimony-tin-titanium precursor solution; the coating, drying and sintering process parameters and number of repetitions of the bottom layer are exactly the same as those in Example 1, forming an Sb-SnO2-TiO2 mixed oxide bottom layer on the surface of the titanium mesh.

[0035] The raw material ratio, slurry preparation and preparation process of the intermediate layer are the same as those in Example 1, forming a Ti4O7-TiO2 mixed oxide intermediate layer on the bottom surface; the precursor preparation and preparation process of the surface layer are the same as those in Example 1, and finally a titanium mesh-based multilayer composite oxide coating sample is obtained.

[0036] Electrochemical polarization test results as follows Figure 4 As shown, the electrochemical polarization potential of the sample in this embodiment is 1.089V, which is slightly higher than that in Example 1. After the molar proportion of titanium in the bottom layer is increased, the coating still maintains a low electrochemical polarization potential, indicating that the adjustment of the bottom layer composition within this range has little impact on the surface conductivity stability, and the overall electrochemical stability of the coating is good.

[0037] Accelerated corrosion life test results are as follows Figure 5 As shown, the accelerated corrosion lifetime of the sample in this embodiment is 195 hours, which is lower than that in Example 1. The increased proportion of titanium in the substrate will reduce the conductivity and oxygen barrier properties of the substrate to a certain extent, thus accelerating the passivation process of the substrate.

[0038] Example 3: The surface pretreatment steps of the titanium mesh in this example are the same as those in Example 1, resulting in a pretreated titanium mesh.

[0039] The preparation process of the antimony-tin-titanium precursor solution and the preparation process of the bottom layer are exactly the same as in Example 1. The Sb, Sn and Ti elements are added in a molar ratio of 10:90:20. After multiple coatings, drying and sintering, an Sb-SnO2-TiO2 mixed oxide bottom layer is formed on the surface of the pretreated titanium mesh.

[0040] The core difference between this embodiment and Example 1 lies in the ratio of raw materials for the intermediate layer: the materials are weighed according to the mass ratio of Ti4O7 powder to tetrabutyl titanate of 5:5, mixed in anhydrous ethanol, and polyvinylpyrrolidone is introduced as a dispersing agent. A uniform slurry is prepared by ultrasonic dispersion and magnetic stirring. The coating, drying, and sintering process parameters and the number of repetitions of the intermediate layer are the same as in Example 1. Finally, a Ti4O7-TiO2 mixed oxide intermediate layer is formed on the surface of the bottom layer.

[0041] The precursor formulation and preparation process of the surface layer are exactly the same as in Example 1. The Ru, Ir, and Ti elements are added in a molar ratio of 25:20:55. After multiple coatings, drying and sintering, a RuO2-IrO2-TiO2 mixed oxide surface layer is formed on the surface of the intermediate layer, and finally a titanium mesh-based multilayer composite oxide coating sample is obtained.

[0042] Electrochemical polarization test results as follows Figure 4 As shown, the electrochemical polarization potential of the sample in this embodiment is 1.093V, which is slightly higher than that in Example 1. The reduced proportion of Ti4O7 in the intermediate layer slightly decreases the overall conductivity of the coating, resulting in a slight increase in the interfacial polarization potential, but it is still at a low level. The coating maintains good conductivity and electrochemical stability.

[0043] Accelerated corrosion life test results are as follows Figure 5 As shown, the accelerated corrosion lifetime of the sample in this embodiment is 195 hours, which is lower than that in Example 1. The increased proportion of titanium in the substrate will reduce the conductivity and oxygen barrier properties of the substrate to a certain extent, thus accelerating the passivation process of the substrate.

[0044] Example 4: The surface pretreatment steps of the titanium mesh in this example are the same as those in Example 1, resulting in a pretreated titanium mesh.

[0045] The preparation process of the antimony-tin-titanium precursor solution and the preparation process of the bottom layer are exactly the same as in Example 1. The Sb, Sn and Ti elements are added in a molar ratio of 10:90:20. After multiple coatings, drying and sintering, an Sb-SnO2-TiO2 mixed oxide bottom layer is formed on the surface of the pretreated titanium mesh.

[0046] The core difference between this embodiment and Example 1 lies in the ratio of raw materials for the intermediate layer: the materials are weighed according to the mass ratio of Ti4O7 powder to tetrabutyl titanate of 4:6, mixed in anhydrous ethanol, and polyvinylpyrrolidone is introduced as a dispersing agent. A uniform slurry is prepared by ultrasonic dispersion and magnetic stirring. The coating, drying, and sintering process parameters and the number of repetitions of the intermediate layer are the same as in Example 1. Finally, a Ti4O7-TiO2 mixed oxide intermediate layer is formed on the surface of the bottom layer.

[0047] The precursor formulation and preparation process of the surface layer are exactly the same as in Example 1. The Ru, Ir, and Ti elements are added in a molar ratio of 25:20:55. After multiple coatings, drying and sintering, a RuO2-IrO2-TiO2 mixed oxide surface layer is formed on the surface of the intermediate layer, and finally a titanium mesh-based multilayer composite oxide coating sample is obtained.

[0048] Electrochemical polarization test results as follows Figure 4 As shown, the electrochemical polarization potential of the sample in this embodiment is 1.095V, which is slightly higher than that of Examples 1 and 3. The proportion of Ti4O7 in the intermediate layer is further reduced, and the overall conductivity of the coating decreases accordingly, resulting in an increase in the interfacial polarization potential, but it is still maintained at a low level. The coating has good conductivity and electrochemical stability.

[0049] Accelerated corrosion life test results are as follows Figure 5 As shown, the accelerated corrosion lifetime of the sample in this embodiment is 168 hours, which is the lowest value among the four sets of embodiments. The further decrease in the Ti4O7 content of the intermediate layer weakens its conductivity enhancement and stress buffering effect, resulting in a reduction in the overall durability of the coating.

[0050] Comparative Example 1: The surface pretreatment steps of the titanium mesh in this comparative example are the same as those in Example 1, resulting in a pretreated titanium mesh.

[0051] The core difference between this comparative example and Example 1 is that the Sb-SnO2-TiO2 mixed oxide underlayer is not set, and the intermediate layer is directly prepared on the surface of the pretreated titanium mesh. The raw material ratio, slurry preparation and preparation process of the intermediate layer are exactly the same as those in Example 1. The Ti4O7 powder and tetrabutyl titanate are fed in a mass ratio of 6:4. After multiple coatings, drying and sintering, a Ti4O7-TiO2 mixed oxide intermediate layer is formed on the surface of the titanium mesh.

[0052] The precursor formulation and preparation process of the surface layer are exactly the same as in Example 1. The Ru, Ir and Ti elements are added in a molar ratio of 25:20:55. After multiple coatings, drying and sintering, a RuO2-IrO2-TiO2 mixed oxide surface layer is formed on the surface of the intermediate layer, and finally the comparative sample is obtained.

[0053] Electrochemical polarization test results as follows Figure 4As shown, the electrochemical polarization potential of this comparative sample is 1.094V, which is similar to that of the sample in the example. The lack of the bottom layer has little impact on the initial conductivity and electrochemical stability of the coating. The high conductivity of the intermediate layer itself can ensure the electron supply of the surface functional phase and maintain a low interface polarization potential.

[0054] Accelerated corrosion life test results are as follows Figure 5 As shown, the accelerated corrosion life of this comparative sample is only 91 hours, which is much lower than that of all the sample examples. It lacks the oxygen barrier effect of the Sb-SnO2-TiO2 underlayer. During corrosion or oxidation, oxygen atoms can diffuse directly into the titanium substrate, quickly forming a high-resistance passivation layer on the substrate surface, causing coating blistering and peeling, which greatly shortens the service life of the coated sample. This confirms the key role of the underlayer in inhibiting substrate passivation and improving long-term stability.

[0055] Comparative Example 2: The surface pretreatment steps of the titanium mesh in this comparative example are the same as those in Example 1, resulting in a pretreated titanium mesh.

[0056] The preparation process of the antimony-tin-titanium precursor solution and the preparation process of the bottom layer are exactly the same as in Example 1. The Sb, Sn and Ti elements are added in a molar ratio of 10:90:20. After multiple coatings, drying and sintering, an Sb-SnO2-TiO2 mixed oxide bottom layer is formed on the surface of the pretreated titanium mesh.

[0057] The core difference between this comparative example and Example 1 is that the Ti4O7-TiO2 mixed oxide intermediate layer is not set. Instead, the surface layer is prepared directly on the bottom layer. The precursor preparation and preparation process of the surface layer are exactly the same as those in Example 1. The Ru, Ir and Ti elements are added in a molar ratio of 25:20:55. After multiple coatings, drying and sintering, the RuO2-IrO2-TiO2 mixed oxide surface layer is directly formed on the bottom layer, resulting in the comparative sample.

[0058] Electrochemical polarization test results as follows Figure 4 As shown, the electrochemical polarization potential of this comparative sample is 1.10V, which is higher than that of all other sample examples. It lacks the conductivity enhancement effect of the Ti4O7-TiO2 intermediate layer, which increases the resistance of the electron conduction path from the matrix to the surface functional phase, resulting in an increase in the interface polarization potential and a decrease in conductivity protection performance.

[0059] Accelerated corrosion life test results are as follows Figure 5 As shown, the accelerated corrosion life of this comparative sample was 122 hours, which was significantly lower than that of the four sets of example samples. Without the stress buffering effect of the intermediate layer, the thermal mismatch stress between the bottom layer and the surface layer could not be effectively released. During high-temperature sintering and corrosion cycling, interlayer cracking and peeling were prone to occur. At the same time, the overall oxygen barrier capacity was reduced, which accelerated the coating failure process. This confirms the key role of the intermediate layer in optimizing interlayer bonding and improving service stability.

[0060] Comparative Example 3: The surface pretreatment steps of the titanium mesh in this comparative example are the same as those in Example 1, resulting in a pretreated titanium mesh.

[0061] The preparation process of the antimony-tin-titanium precursor solution and the preparation process of the bottom layer are exactly the same as in Example 1. The Sb, Sn and Ti elements are added in a molar ratio of 10:90:20. After multiple coatings, drying and sintering, an Sb-SnO2-TiO2 mixed oxide bottom layer is formed on the surface of the pretreated titanium mesh.

[0062] The core difference between this comparative example and Example 1 lies in the composition of the intermediate layer: pure Ti4O7 powder was used to prepare the slurry, without adding tetrabutyl titanate as a binder phase. Ti4O7 powder was added to anhydrous ethanol, and polyvinylpyrrolidone was introduced as a dispersing agent. The slurry was uniformly dispersed by ultrasonic dispersion and magnetic stirring. The coating, drying, and sintering process parameters and number of repetitions of the intermediate layer were the same as in Example 1, and finally a pure Ti4O7 intermediate layer was formed on the surface of the bottom layer.

[0063] The precursor formulation and preparation process of the surface layer are exactly the same as in Example 1. The Ru, Ir, and Ti elements are added in a molar ratio of 25:20:55. After multiple coatings, drying and sintering, a RuO2-IrO2-TiO2 mixed oxide surface layer is formed on the surface of the intermediate layer, resulting in a comparative sample.

[0064] Electrochemical polarization test results as follows Figure 4 As shown, the electrochemical polarization potential of this comparative sample is 1.085V, which is slightly lower than that of Example 1. The intrinsic conductivity of pure Ti4O7 is better, which can further reduce the electronic conduction resistance, resulting in a slight decrease in the interface polarization potential and better initial conductivity protection performance.

[0065] Accelerated corrosion life test results are as follows Figure 5 As shown, the accelerated corrosion life of this comparative sample is 140 hours, which is lower than that of the four sets of example samples. Without the TiO2 binder phase, the sintering bonding strength between Ti4O7 particles is insufficient. Under corrosion conditions, active particles are prone to detachment and loss, resulting in decreased interlayer structural stability and accelerated coating failure. This result confirms that the Ti4O7-TiO2 composite intermediate layer of this invention can enhance particle bonding strength while ensuring conductivity, thereby achieving a synergistic improvement in conductivity protection performance and service life.

[0066] In summary, combining Figure 4 and Figure 5Electrochemical polarization potential characterizes the electrochemical stability of the coating. The electrochemical polarization potentials of the four sets of sample examples range from 1.087V to 1.095V, which is generally low, indicating good conductivity and electrochemical stability. Comparative Example 3 has the lowest electrochemical polarization potential among all samples. The high intrinsic conductivity of the pure Ti4O7 interlayer can further reduce the electron conduction resistance, resulting in a slight decrease in the interface polarization potential. Comparative Example 2 has the highest electrochemical polarization potential. Without the conductivity enhancement effect of the Ti4O7-TiO2 interlayer, the resistance of the electron conduction path from the matrix to the surface functional phase increases, directly leading to an increase in the interface polarization potential. In the examples, as the proportion of TiO2 binder phase in the interlayer increases and the proportion of titanium element in the bottom layer increases, the electrochemical polarization potential shows a slight increase, indicating that changes in the proportion of conductive phase can have a fine-tuning effect on electron conduction efficiency. However, the three-layer composite structure as a whole can still ensure sufficient electron conduction efficiency.

[0067] Accelerated corrosion lifetime reflects the long-term service stability of the coating. The accelerated corrosion lifetimes of all four examples were significantly higher than those of the three comparative examples. Example 1 achieved the best performance among all samples with 221 hours, while Comparative Example 1 had the lowest accelerated corrosion lifetime at only 91 hours. Without the oxygen barrier effect of the Sb-SnO2-TiO2 underlayer, oxygen atoms could directly diffuse to the titanium substrate surface during corrosion or oxidation, rapidly forming a high-resistance passivation layer and causing blistering and peeling of the coating, directly accelerating the failure process of the coating sample. Comparative Example 2 had an accelerated corrosion lifetime of 122 hours. Without the stress buffering effect of the intermediate layer, the mismatch in thermal expansion coefficients between the underlayer and the surface layer could not be alleviated, leading to continuous accumulation of interlayer thermal stress, which easily caused interlayer cracking and active layer detachment. Comparative Example 3 had an accelerated corrosion lifetime of 140 hours, still lower than all examples. The pure Ti4O7 particles lacked the consolidation and binding of the TiO2 binder phase, making them prone to detachment and loss during high-temperature sintering and corrosion cycling, failing to maintain long-term structural stability.

[0068] The two sets of performance data jointly verified the synergistic effect of the three-layer composite structure. The Sb-SnO2-TiO2 bottom layer plays a role in oxygen barrier and interfacial bonding, delaying substrate passivation; the Ti4O7-TiO2 intermediate layer simultaneously achieves stress buffering and conductivity enhancement, adapts to the thermal expansion characteristics of the upper and lower layers, and ensures efficient electron transport; the RuO2-IrO2-TiO2 surface layer provides stable conductivity and corrosion resistance. Under the synergistic effect of the three, the coating can significantly improve the interfacial bonding strength and electrochemical corrosion resistance while maintaining good conductivity, achieving simultaneous optimization of conductivity protection performance and long-term service stability, fully verifying the effectiveness and superiority of the technical solution of this invention.

[0069] In summary, this invention utilizes a three-layer composite coating structure to sequentially prepare a Sb-SnO2-TiO2 mixed oxide underlayer, a Ti4O7-TiO2 mixed oxide intermediate layer, and a RuO2-IrO2-TiO2 mixed oxide surface layer on a titanium mesh substrate. This structure achieves synergistic effects through the compositional design and process adaptation of each functional layer. The underlayer, constructed with antimony-doped tin-based oxide, forms a dense oxygen barrier and interface transition layer, inhibiting the formation of a passivation layer on the titanium mesh substrate surface during corrosion or oxidation, while providing a stable bonding surface for the upper coating layer. The intermediate layer uses highly conductive Ti4O7 as the functional phase and pyrolytic TiO2 as the binder phase, adapting to the thermal expansion characteristics of the upper and lower layers to alleviate interlayer thermal stress, while simultaneously enhancing electron conduction efficiency and interlayer bonding strength. The surface layer uses a noble metal composite oxide as the functional phase, providing stable conductivity and corrosion resistance. This technical solution effectively improves the defects of traditional titanium mesh surface protective coatings, such as weak interfacial bonding, easy passivation and peeling, and insufficient service stability. While maintaining good conductivity, it significantly improves the coating's resistance to electrochemical corrosion and structural durability, achieving simultaneous optimization of the coating's conductive protection performance and long-term service life.

[0070] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, apparatus, article, or method that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, apparatus, article, or method. Unless otherwise specified, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, apparatus, article, or method that includes that element.

[0071] The above description is merely a preferred embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural or procedural transformations made based on the content of the present invention's specification and drawings, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.

Claims

1. A method for preparing a multilayer composite oxide protective coating on a titanium mesh surface by thermal decomposition, characterized in that, Includes the following steps: S1, perform surface pretreatment on the titanium mesh to obtain a pretreated titanium mesh; S2, an antimony-tin-titanium precursor solution is coated on the surface of a pretreated titanium mesh, dried and sintered in an air atmosphere at 480~520℃. The coating, drying and sintering are repeated multiple times to form a mixed oxide underlayer of Sb-SnO2-TiO2 on the surface of the titanium mesh. S3, a mixed slurry containing titanium heptoxide and a titanium source is coated on the surface of the Sb-SnO2-TiO2 mixed oxide bottom layer, dried and sintered in an air atmosphere at 530~570℃, and the coating, drying and sintering are repeated multiple times to form a Ti4O7-TiO2 mixed oxide intermediate layer. The mixed slurry was prepared by adding Ti4O7 powder and tetrabutyl titanate in anhydrous ethanol at a mass ratio of 4:6 to 6:4, adding polyvinylpyrrolidone, and then dispersing and stirring with ultrasound and magnetic force. The mixed slurry is coated onto the surface of the Sb-SnO2-TiO2 mixed oxide substrate, dried at 100°C for 8-12 minutes, and then placed in a muffle furnace for air atmosphere sintering. The sintering time for each sintering is 25-35 minutes. S4, a ruthenium-iridium-titanium precursor solution is coated on the surface of the Ti4O7-TiO2 mixed oxide intermediate layer, dried, and then sintered in an air atmosphere at 480~520℃. The coating, drying, and sintering are repeated multiple times to form a RuO2-IrO2-TiO2 mixed oxide surface layer.

2. The method for preparing a multilayer composite oxide protective coating on a titanium mesh surface by thermal decomposition according to claim 1, characterized in that, The molar ratio of Sb, Sn, and Ti in the antimony-tin-titanium precursor solution in step S2 is 10:90:20 to 10:90:

30.

3. The method for preparing a multilayer composite oxide protective coating on a titanium mesh surface by thermal decomposition according to claim 1, characterized in that, The antimony-tin-titanium precursor solution in step S2 is prepared by dissolving antimony trichloride, tin tetrachloride and tetrabutyl titanate in a mixed solvent of isopropanol and n-butanol, and then adding concentrated hydrochloric acid.

4. The method for preparing a multilayer composite oxide protective coating on a titanium mesh surface by thermal decomposition according to claim 1, characterized in that, In step S4, the molar ratio of Ru, Ir, and Ti in the ruthenium-iridium-titanium precursor solution is 25:20:

55.

5. The method for preparing a multilayer composite oxide protective coating on a titanium mesh surface by thermal decomposition according to claim 1, characterized in that, The coating method described in steps S2 and S4 is brush coating, the drying temperature is 95℃~105℃, the drying time is 8~12min, and the single sintering time is 25~35min.

6. The method for preparing a multilayer composite oxide protective coating on a titanium mesh surface by thermal decomposition according to claim 1, characterized in that, Step S1 includes: The titanium mesh was sandblasted with 60-mesh white corundum to control the surface roughness Ra to be 5μm~7μm; The sandblasted titanium mesh was placed in an environment of 480℃~520℃ for 40min~50min for stress relief heat treatment, and then cooled to room temperature in the furnace. Prepare an oxalic acid solution with a mass fraction of 5%–7% and pickle the titanium mesh at 80℃–90℃ for 2.5h–3.5h. After pickling, the titanium mesh is ultrasonically cleaned with pure water 3 to 5 times, with each cleaning session lasting 10 to 14 minutes. Then it is dried in an environment of 65℃ to 75℃ to obtain the pretreated titanium mesh.

7. The method for preparing a multilayer composite oxide protective coating on a titanium mesh surface by thermal decomposition according to claim 1, characterized in that, In step S2, the coating, drying and sintering are repeated 2 to 4 times; in step S3, the coating, drying and sintering are repeated 2 to 4 times; and in step S4, the coating, drying and sintering are repeated 7 to 9 times.

8. A multilayer composite oxide protective coating on the surface of a titanium mesh, characterized in that, include: Titanium mesh; The titanium mesh is sequentially covered with a bottom layer of Sb-SnO2-TiO2 mixed oxide, an intermediate layer of Ti4O7-TiO2 mixed oxide, and a top layer of RuO2-IrO2-TiO2 mixed oxide.

9. The multilayer composite oxide protective coating on the titanium mesh surface according to claim 8, characterized in that, In the bottom layer of the Sb-SnO2-TiO2 mixed oxide, the molar ratio of Sb, Sn, and Ti is 10:90:20 to 10:90:30; in the surface layer of the RuO2-IrO2-TiO2 mixed oxide, the molar ratio of Ru, Ir, and Ti is 25:20:

55.

10. The multilayer composite oxide protective coating on the titanium mesh surface according to claim 8, characterized in that, The Ti4O7-TiO2 mixed oxide intermediate layer is prepared by sintering Ti4O7 powder and tetrabutyl titanate in a mass ratio of 4:6 to 6:4.